The Hidden Impact of Gestational Diabetes: Unveiling Offspring Complications and Long-Term Effects - Elsa Al Bekai; Carla El Beaini; Karim Kalout; Ouhaila Safieddine; Sandra Semaan; François Sahyoun; Hilda E. Ghadieh; Sami Azar; Amjad Kanaan; Frederic Harb (Life)
Background: Gestational diabetes mellitus (GDM), characterized by gestational hyperglycemia due to insufficient insulin response, poses significant risks to both maternal and offspring health. Fetal exposure to maternal hyperglycemia leads to short-term complications such as macrosomia and neonatal hypoglycemia and long-term risks including obesity, metabolic syndrome, cardiovascular dysfunction, and type 2 diabetes. The Developmental Origins of Health and Disease (DOHaD) theory explains how maternal hyperglycemia alters fetal programming, increasing susceptibility to metabolic disorders later in life. Objective: This review explores the intergenerational impact of GDM, linking maternal hyperglycemia to lifelong metabolic, cardiovascular, and neurodevelopmental risks via epigenetic and microbiome alterations. It integrates the most recent findings, contrasts diagnostic methods, and offers clinical strategies for early intervention and prevention. Methods: A comprehensive literature search was conducted in PubMed, Scopus, and ScienceDirect to identify relevant studies published between 1 January 2000 and 31 December 2024. The search included studies focusing on the metabolic and developmental consequences of GDM exposure in offspring, as well as potential mechanisms such as epigenetic alterations and gut microbiota dysbiosis. Studies examining preventive strategies and management approaches were also included. Key Findings: Maternal hyperglycemia leads to long-term metabolic changes in offspring, with epigenetic modifications and gut microbiota alterations playing key roles. GDM-exposed children face increased risks of obesity, glucose intolerance, and cardiovascular diseases. Early screening and monitoring are crucial for risk reduction. Practical Implications: Understanding the intergenerational effects of GDM has important clinical implications for prenatal and postnatal care. Early detection, lifestyle interventions, and targeted postnatal surveillance are essential for reducing long-term health risks in offspring. These findings emphasize the importance of comprehensive maternal healthcare strategies to improve long-term outcomes for both mothers and their children.